Syukor / Mohd Syazrul Hafizi Husin and Anita Abu Hassan - Husin, Mohd Syazrul Hafizi; Abu Hassan, Anita (Faculty of Art and Design, 2021)
Mohd Syukor Khamis or known as Syukor is an exceptional child when it comes to building up the bonding with nature particularly with animals and this has made Syukor famously known as "Mowgli Malaysia". He currently lives in a place called Kuala Terengganu, a district within the state of Terengganu. At present, Syukor is attending his formal schooling at Sekolah Menengah Kebangsaan (SMK) Padang Midin. From an early age, he has been exposed to the surroundings that are full of life of the other species. A special trait about Syukor is that he has a very close relationship with the buffaloes owned by his father. The love and the care he shows to the buffaloes and the acceptance of the buffaloes as Syukor is part of the herd evidencing from the affection shown between a human child and the buffaloes in all published photos are so magnificent. A photographer named Yusuf Madi is the person who introduces Syukor to the outside world. The chosen pictures used for this work of art have succeeded Yusuf Madi to become a winner for August 2020 Asian Geographic under streets / people categories.